Clinical impacts of sun exposures on the faces and hands of Japanese women of different ages. (3rd October 2019) - Flament, F.; Velleman, D.; Yamamoto, S.; Nicolas, A.; Udodaira, K.; Yamamoto, S.; Morimoto, C.; Belkebla, S.; Negre, C.; Delaunay, C.
Abstract: Objective: To assess the impacts of sun exposures on some skin signs on the faces and hands of differently aged Japanese women, according to their distinct behaviours towards vis à vis sun exposure. Methods: Two comparable cohorts of Japanese women (aged 18–83 years) were created according to their usual behaviour towards sun exposure i.e. non‐sun‐phobic ( N  = 495) and sun‐phobic ( N  = 516) and through their regular use(s) of a photo‐protective product. Standard photographs (full‐face and 45° lateral) allowed to focus on 18 facial signs that were graded by 15 experts, using a referential skin ageing Atlas. From these two cohorts, two sub‐cohorts (114 and 122 women) were created with regard to the similar clinical aspects of the dorsal side of their hands (Left vs. Right) that were further graded. Absolute differences in the scores of each sign were used (non‐sun‐phobic minus sun‐phobic), by age‐ranges, to better ascertain the impact of sun exposures and photo‐protection. Results: Facial signs related to skin wrinkles/texture and pigmentary spots were found significantly more accentuated among non‐sun‐phobic women and show an early onset (20–30 years). Facial sagging and crow's feet wrinkles appear delayed (30–40 years). The severity of vascular disorders was found to be similar in the two cohorts. The absolute differences in the grading's of almost all signs were unsurprisingly found increased with advancing ages, illustrating the combination of chronological and photo‐ageing processes. With regard to hands, differences in skin texture and pigmentary disorders are of a late onset (40–50 years) and were found much increased at older ages. The cutaneous signs of the hands of Japanese women can hardly be taken as reliable markers of their photo‐ageing status. Conclusion: The present work illustrates, for the first time, some specificities of the impact of sun exposures on the facial skin of Japanese women, pinpointing the fact that some facial signs are of an early onset. Results significantly confirm the importance of both sun avoidance coupled with photo‐protective measures. Abstract : Illustrative examples of sun exposures' clinical impact on NSP (left) and SP (right) on two pictures (Front‐full face and 45° lateral). Both subjects are of same age (71 years old). Résumé: Objectif: D'évaluer les impacts de l'exposition solaire sur plusieurs signes du visage et des mains de femmes Japonaises d'âge différents, selon leurs différents comportements vis‐à‐vis de l'exposition solaire. Méthodes: Deux cohortes comparables de femmes Japonaises (âgées de 18 à 83 ans) ont été créées selon leur comportement habituel vis à vis de l'exposition solaire, phobique ( N  = 516) ou non ( N  = 495) et selon leur utilisation(s) régulière(s) de produits photo‐protecteurs. Des photographies standardisées du visage de face et latérales (45°) ont permis de se focaliser sur 18 signes cliniques du visage dont la sévérité a été quantifiée par 15 experts, utilisant un Atlas de référence du vieillissement cutané. De ces deux cohortes, deux sous‐cohortes ont été extraites (114 et 122 femmes) par les aspects cliniques similaires de la face dorsale de leurs mains (Gauche vs. Droite) pour être ensuite quantifiées. Les différences absolues de chaque signe (non‐phobiques moins phobiques), par tranches d'âges, ont été utilisées pour mieux déterminer l'impact des expositions solaires et des routines de photo‐protection. Résultats: Les signes du visage liés à la texture cutanée/rides et aux taches pigmentaires ont été trouvés significativement aggravés chez les femmes non‐phobiques de l'exposition solaire et d'apparition précoce (20–30 ans) tandis que la ptose du visage ou les rides de la patte d'oie apparaissent plus tardivement (30–40 ans). La sévérité des désordres vasculaires du visage a été trouvée similaire dans les deux cohortes. Les différences absolues dans la sévérité de la plupart des signes ont été logiquement trouvées accrues avec l'âge, illustrant la combinaison du vieillissement chronologique et de celui photo‐induit. Concernant les mains, les différences dans la texture cutanée et les désordres pigmentaires apparaissent significativement tardives (40–50 ans) et augmentent à des âges plus avancés. Les signes cutanés des mains des femmes Japonaises ne semblent donc pas être des marqueurs fiables du vieillissement photo‐induit. Conclusion: La présente étude illustre, pour la première fois, quelques spécificités des impacts de l'exposition solaire sur les signes faciaux de femmes Japonaises, pointant le fait que certains sont d'apparition précoce. Les résultats confirment de manière significative l'importance d'éviter les expositions solaires et de recourir à des mesures photo‐protectrices.